Light-Absorbing Impurities on Urumqi Glacier No.1 in Eastern Tien Shan: Concentrations and Implications for Radiative Forcing Estimates During the Ablation Period - Zhang, Xin; Li, Zhongqin; You, Xiaoni; She, Yuanyang; Song, Mengyuan; Zhou, Xi (Frontiers in Earth Science, 2021)
Light-absorbing impurities (LAIs) in surface snow and snow pits together with LAIs concentrations and their impacts on albedo reduction and sequent radiative forcing (RF) have been investigated in the past. Here we focused on temporal-spatial distributions of LAIs, especially on the albedo reduction and radiative forcing caused by the LAIs in Urumqi Glacier No.1. Various snow samples, including fresh snow, aged snow, and granular ice were collected at between 3770 and 4105 m a.s.l of Urumqi Glacier No.1 during the snowmelt season of 2015. For the surface snow samples, BC and OC concentrations were 582 ng g-1 and 1590 ng g-1, respectively. Mineral dust (MD) concentrations were 110 μg g-1. Due to the different ablation status of the glacier surface, LAIs accumulate at the lower altitude of the glacier. The estimation by Snow, Ice, and Aerosol Radiative (SNICAR) model indicated that BC and MD could reduce the albedo by 12.8% and 10.3% in fresh snow, aged snow by 23.3%, and 5.9%, and granular ice by 22.4% and 26.7%, respectively. The RF of MD was higher than that of BC in fresh snow and granular ice, whereas the RF of BC exceeded MD in aged snow. These findings suggested that BC was the main forcing factor in snow melting and dust was the main forcing factor in accelerating glacier melt.